2012
DOI: 10.1021/jf3036462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Iron Application on Iron Concentration in Polished Rice Grain and Its Bioavailability

Abstract: Iron (Fe) deficiency in humans caused by inadequate dietary intake is a global nutritional problem. A glass house pot experiment was conducted to evaluate the effect of foliar FeSO₄ containing applications on concentrations of Fe, Zn, and Fe bioavailability in polished rice among five rice cultivars. The results showed that foliar application of FeSO₄, FeSO₄, plus nicotianamine (NA), and FeSO₄ plus NA with ZnSO₄ increased the grain Fe concentration by 16.97%, 29.9%, and 27.08%, respectively. The grain Fe bioav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 33 publications
6
45
0
1
Order By: Relevance
“…Late season foliar application of Zn or Fe at flowering or at early grain filling stage is more effective in improving grain Zn or Fe, respectively, than early season application (Phattarakul et al, 2012; Mabesa et al, 2013). Though the levels of Zn and Fe in grains are positively related, fertilization of one element did not affect the grain concentration of the other (Cakmak et al, 2010; Wei et al, 2012a,b). However, foliar fertilization of combined Fe and Zn fertilizers enhanced both grain-Fe and -Zn content without any antagonistic effects (Wei et al, 2012a).…”
Section: Fertilization Optionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Late season foliar application of Zn or Fe at flowering or at early grain filling stage is more effective in improving grain Zn or Fe, respectively, than early season application (Phattarakul et al, 2012; Mabesa et al, 2013). Though the levels of Zn and Fe in grains are positively related, fertilization of one element did not affect the grain concentration of the other (Cakmak et al, 2010; Wei et al, 2012a,b). However, foliar fertilization of combined Fe and Zn fertilizers enhanced both grain-Fe and -Zn content without any antagonistic effects (Wei et al, 2012a).…”
Section: Fertilization Optionsmentioning
confidence: 89%
“…Under aerobic water management, the soil-applied Fe (usually in the form of Fe 2+ , either chelated or as a sulfate salt) is rapidly converted to unavailable Fe 3+ , and hence, foliar application is a better option to overcome Fe deficiency and to increase grain Fe and its bioavailability in rice (Wei et al, 2012a). Under anaerobic water management, Fe 2+ is readily available to rice plants ( Figure 1 ), so no fertilization is needed.…”
Section: Fertilization Optionsmentioning
confidence: 99%
“…In these crops, which are generally treated with foliar iron sprays when there is no leaf chlorosis, applied iron has been shown to re-translocate efficiently to other plant organs, both in wheat and rice (Wei et al, 2012). Zuo and Zhang (2011) have developed strategies to increase iron 28 F. D. Oeste et al: Climate engineering by mimicking natural dust climate control uptake by roots and transfer it to edible plant portions, allowing absorption by humans from plant food sources.…”
Section: Importance Of Iron For Human Food and Healthmentioning
confidence: 99%
“…Previous studies have demonstrated that some mineral elements are abundant in the rice aleurone layer and embryo but less so in the endosperm (Bouis and Welch, 2010;Wei, et al, 2012a). Unfortunately the form of rice most commonly globally consumed is milled rice, which endosperm with the aleurone layer and embryo removed.…”
Section: Introductionmentioning
confidence: 99%
“…Some screening studies have identified Fe-and Zndense genotypes with the aim of enhancing the mineral nutrition concentrations in milled rice (Sperotto et al, 2012;Wei et al, 2012a). Previous studies have also investigated the effects of fertilizer on the mineral element concentrations in milled rice, including the effects of fertilizer type, application pattern and application amount (Zhang et al, 2007;Wei et al, 2012a;He et al, 2013). Yuan et al (2006) reported that the optimal application of N fertilizer in paddy fields was instrumental in the accumulation of Fe, Cu, Mn, Zn, Ca and Mg in milled rice.…”
Section: Introductionmentioning
confidence: 99%